قۆناغە كردەییەكانی زمانوەرگرتن لای منداڵ - حسەین, ئازاد ئەحمەد; عەبدولوەهاب, عەدنان عەبدوڵڵا (Sulaimani Journal for Humanities, 2022)
This research, entitled (The practical stages of language acquisition in a child), talks about that the child is born with a natural ability, to teach human behavior and acquire language in particular, but the emergence and progress of this ability is linked to the development of the biological, psychological and social aspect.And this development in the child is a simple process, because when they come to life, the appropriate ground has been prepared for them from the biological foundation and the family and social environment.What is important here are the stages of the process, such as: )The stage of crying - screaming, the stage of babbling , and the stage of learning the word). The research reached several results, including: The first consonant sound, which the child learns in the babbling stage and crosses, is the sound (G), even though this letter is weak in some languages, such as the Kurdish language.And that when the child acquires language, the negation and the question tool appear early.Compared to tools (knowledge, indefinite, plural,...etc).